Fibrinogen and Coronary Artery Disease A Review - Ahmed, Mohsin; Chowdhury, Nazir Ahmed; Sofdar, Gulshan; Rahman, Md Zillur; Majumder, Abdullah Al Shafi (University Heart Journal, 2014)
No Abstract DOI: http://dx.doi.org/10.3329/uhj.v9i1.19510 University Heart Journal Vol. 9, No. 1, January 2013; 40-46